ACCULTURATION OF ISLAMIC CULTURE AND LOCAL CULTURE IN DRUMING TRADITION IN PANJANG REGION VILLAGE, KUCHING, SARAWAK, MALAYSIA - Mohammad Shafiq Bin Asan (Batuthah: Jurnal Sejarah Padaban Islam, 2024)
This article focuses on the acculturation of Islamic culture and local culture in the Bergendang tradition. The purpose of writing this article is to preserve the traditions that have been carried out by the Rantau Panjang Malay community in order to introduce them to the public. The approach and theoretical framework used in this research is the cultural anthropology approach and acculturation theory with a functional approach. Meanwhile, the methods used are ethnographic methods and phenomenological methods. From this research, it can be found that the background to the emergence of the Drumming tradition in Kampung Rantau Panjang is related to the absence of entertainment in ancient times, encouraging the people to create offerings to fill their free time and provide entertainment. In this case, previous people started the tradition of drumming by tapping on used boards and it produced different sounds and could arouse people's interest in dancing to the sound of used boards being hit. The developments and changes that have occurred have helped the Bergendang tradition continue to be in demand by every level of society. Even though some structures have changed, this traditional entertainment still maintains the elements and rules of the event. Apart from that, Islamic values ​​have become the spirit of various aspects in the implementation of the Bergendang tradition. Then, the majority of the people of Kampung Rantau Panjang responded to the implementation of the Bergendang tradition with a positive response. This can be seen from the enthusiasm of the residents when carrying out this tradition.